MENINGKATKAN PENJUALAN SECARA DIGITAL MARKETING DAN SERTIFIKASI PRODUK HALAL UMKM KECAMATAN TINGKIR KOTA SALATIGA - Harminingtyas, Rudika; Prabowo, Catur; Fahlefi, Diva Riza; Tasriastuti, Nurrohmi Ambar; Widowati, Maduretno (Fokus ABDIMAS, 2024)
Salatiga is a city located in Central Java Province, Indonesia. This city is known as a cool area because it is located on the slopes of Mount Ungaran. Salatiga has a rich history and is a comfortable place to live as well as a center of government, economy and recreation. Tingkir is also a sub-district in Salatiga City, Central Java Province. Basically, MSMEs are a productive business or business that is run by individuals, groups, households, or small business entities that meet the standards as micro-businesses. So, it can be concluded that this MSME as a business managed by people from the lower middle class, this MSME aims to expand employment opportunities and provide economic services to the community at large. The characteristics of MSMEs are usually that business actors have not yet gained access to banking, but can access non-banking institutions, Generally do not have a business license, including a Taxpayer Identification Number (NPWP). The place of business can move. The commodity goods produced by the business are not fixed and can change.By looking at the conditions in the field, the MSMEs were given training on improving the use of digital technology which is currently widely used by the community. They feel that what they have done so far has not been optimal because they do not know what to do with technological advances. With this training, they open their hearts and minds to develop their business with the knowledge received during this training, namely marketing through digital media. This training is very helpful for MSMEs in trying to increase sales of their products so that they can cover their operational costs and can get decent profits and do not need to worry about sluggish sales. It is hoped that participants can continue to improve their businesses and use the right technology so that the businesses they run can grow